Effect of storage conditions on the solubility and rennet gelation characteristics of micellar casein concentrate (MCC) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology at Massey University, Palmerston North, New Zealand - Natarajan, Kamalam (Massey University, 2021)
Micellar casein concentrate (MCC) is a microfiltration-produced dairy low-lactose protein ingredient, consisting mainly of casein micelles in their native form with a minimal amount of whey proteins. The physicochemical characteristics and nutritional value of the protein have been utilised in a wide range of food applications such as cheese, yoghurt, ready-to-drink beverages and dairy protein-fortified products. This emerging product benefits the market growth of the dairy industry due to an increase in consumer demand towards protein-fortified foods with all-natural, minimally processed, nutritive value-added protein ingredient. So, it is vital to understand the challenges that manufacturers, supply chain and customers may face on storing the product for a period of time. The purpose of this study was to analyse the influence of storage time (180 days) and temperature (20°C, 30°C and 40°C) on the solubility and rennet gelation characteristics of MCC powder in cheese manufacturing. The solubility of fresh and stored MCC samples was tested under various reconstitution temperatures (25, 30, 35, 40, 50 and 60°C) at 30- and 180-minute hydration times by measuring moisture content and particle size distribution using moisture-dish and Mastersizer respectively. The maximum solubility of the fresh MCC powder was found to be obtained at 50°C hydration temperature with a hydration time of 30 min, which will benefit industry by reducing the dissolving time of the powder. The solubility of stored MCC samples at various rehydration temperatures for different periods was found to decline as the storage time and storage temperature increased for any given hydration temperature. The MCC powder stored at 40°C became completely insoluble after 30 days storage. Even at the room temperature of 20°C, a linear decrease in solubility from 99% to 80% was observed over a storage period of 180 days. The cause for the solubility decline rate in the stored MCC samples was found to be correlated with the browning index (BI) indicating that, despite the low content of lactose, Maillard reactions in the stored samples are the likely cause of insolubility. The combined microstructural analysis of scanning electron microscopy (SEM) and transmission electron microscopy (TEM) gave an insight of particle size, shape and a cross-sectional view of casein micelles in powder particles. However, protein crosslinking was not visible in the stored MCC samples. The study found an alternative industrially available option to improve MCC solubilisation regardless of the storage conditions. By generating shear force using a single-stage high pressure homogeniser to breakdown the particles, solubility was shown to be increased from 63% (the least soluble powder used in this section of the thesis) to 97% in the stored MCC samples. The rheological properties of rennet gels made from skim milk-fortified fresh MCC with two different hydration times of 24 hr and 3 hr were quantified and the results were compared using two dynamic gel firmness tests, Formagraph and Low-amplitude oscillation rheometric (LAOR) analysis. The study found that 3 hr of MCC rehydration gives the optimal gelation properties which will also be benefit industry by reducing the hydration time during protein fortification. Both the test methods yielded comparable results for rennet gelation properties, but, the Formagraph had an advantage of assessing 10 samples at a time. The influence of renneting set temperature (30°C & 32°C) and pH (standard sample’s pH 6.7 and adjusted pH 6.3) on the rennet gelation properties of skim milk-fortified fresh MCC solution tested using only the Formagraph due to comparable results with LAOR and the test’s efficiency. Increasing the renneting set temperature from 30°C to 32°C results in faster gelation time and optimal cutting time with high firmness and firming rate. Pre-acidifying the skim milk-fortified MCC samples to pH 6.3 resulted in faster gelation and cutting time with higher gel firmness and firming rate than the pH 6.7. Due to the project’s time constraints which were magnified by COVID-19 pandemic related lockdown, only five samples were selected to study the rennet gelation properties of stored MCC samples with no modifications done to the experimental set-up conditions such as temperature and pH. As the storage temperature and time increases, the solubility decreased, which resulted in longer gelation and cutting times with weaker gel formation. This study provides novel information on the solubility and rennet gelation properties of MCC and also ingredient functionality with respect to the storage temperature and time. The research presented here has implications for product formulation in an industrial setting.
The following Figures were removed for copyright reasons: 2.6 (=Sosnik & Seremeta, 2015 Fig 1); 2.7 (=Damodaran & Parkin, 2017 Fig p.290) & 2.8 (=Heino, 2010 Fig 6 p.35). Figure 2.3 is re-used under a Creative Commons Attribution 4.0 International License (CC BY 4.0).
Keywords: 300607 Food technology